Immunisation with recombinant modified vaccinia virus Ankara expressing HIV-1 gag in HIV-1-infected subjects stimulates broad functional CD4+ T cell responses. - Ondondo, B; Yang, H; Dong, T; di Gleria, K; Suttill, A; Conlon, C; Brown, D; Williams, P; Rowland-Jones, S; Hanke, T; Mcmichael, A; Dorrell, L (2006)
Virus-specific CD4+ T cells with IL-2-secreting and/or proliferative capacity are detected readily in HIV-1-infected long-term nonprogressors and rarely in persons with untreated progressive infection. The contribution of these cells to viraemia control is uncertain, but this question might be addressed in clinical therapeutic vaccination studies. However, the quality of T helper responses induced by currently available HIV-1 vaccine candidates has not been explored in depth. We determined the effect of vaccination with modified vaccinia virus Ankara (MVA) expressing HIV-1 gag p24/p17 (MVA.HIVA) on HIV-1-specific CD4+ T cell responses in 16 chronically infected, highly active antiretroviral therapy (HAART)-treated subjects using CD8-depleted IFN-gamma ELISPOT assays, intracellular cytokine staining assays for IL-2 and IFN-gamma, and a CFSE-based proliferation assay. Gag-specific CD4+ T cell responses were significantly increased in magnitude and breadth after vaccination and targeted both known and new epitopes, several of which were also recognised by healthy HIV-uninfected volunteers immunised with the same vaccines. The frequencies of CD4+ T cells expressing IL-2 or IFN-gamma, alone or simultaneously, were also augmented. These findings indicate that functional virus-specific T helper cells can be boosted by vaccination in chronic HIV-1 infection. Further evaluation of their role in viraemia control is warranted.